2016
DOI: 10.1186/s13018-016-0386-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of vancomycin-releasing biodegradable poly(lactide-co-glycolide) antibiotics beads for treatment of experimental bone infection due to Staphylococcus aureus

Abstract: BackgroundClinical experience and animal studies have suggested that positron emission tomography (PET) using fluorine-18-labeled fluorodeoxyglucose (18F-FDG) may be promising for imaging of bone infections. In this study, we aimed to establish the accuracy of 18F-FDG PET scanning for monitoring the response to poly(lactide-co-glycolide) (PLGA) vancomycin beads for treatment of bone infection.MethodsPLGA was mixed with vancomycin and hot-compress molded to form antibiotic beads. In vitro, elution assays and ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…7) and planktonic growth experiments (fig. 8) where it was possible to confirm the antibacterial efficiency of same antibiotics for same strain [41][42][43][44][45]. When biofilms were in contact with the unloaded 4ZN-GE scaffolds a partial biofilm destruction was found in both strains which show zinc antibacterial effect by itself.…”
Section: Biofilm Degradationmentioning
confidence: 86%
See 1 more Smart Citation
“…7) and planktonic growth experiments (fig. 8) where it was possible to confirm the antibacterial efficiency of same antibiotics for same strain [41][42][43][44][45]. When biofilms were in contact with the unloaded 4ZN-GE scaffolds a partial biofilm destruction was found in both strains which show zinc antibacterial effect by itself.…”
Section: Biofilm Degradationmentioning
confidence: 86%
“…S. aureus 4ZN-GE scaffolds were loaded with LEVO, VANCO and RIFAM because their referenced effectiveness against S. aureus (Fig. 7.1-3) [41][42][43]. The antibiotic loaded scaffolds were named as 4ZN-GE-L, 4ZN-GE-V and 4ZN-GE-R, respectively.…”
Section: Agar Disk-diffusion Tests Of Drug Loaded Materialsmentioning
confidence: 99%
“…The composite system of the two polymers revealed adequate osteogenic differentiation of mesenchymal stem cells in a rabbit model (Ueng et al., 2011 ). Further in-vitro and in-vivo studies applying the biodegradable PLGA-vancomycin beads confirmed their success in eradicating the induced infection in the damaged bone of rabbits model (Ueng et al., 2016 ).…”
Section: Systems Under Investigation For the Local Delivery Of Antibiotic For Osteomyelitis Managementmentioning
confidence: 89%
“…These technologies include 3D-printing, bacterial genomic sequencing and microbiome profiling, and real-time in vivo imaging modalities. [33][34][35][36][37]134 These technologies have enabled the development of species-specific reproducible implants, 34,134 incorporation of patient risk factors for implant infection into the model (e.g., diabetes, gut microbiome constituents), 32,33 and real-time minimally invasive tracking of infection and inflammation in vivo. 37 Furthermore, the emergence of stimuli-responsive antimicrobial materials (e.g., responsive to temperature, magnetic/electric fields, microwaves, etc.)…”
Section: Discussionmentioning
confidence: 99%